2011
DOI: 10.1073/pnas.1105461108
|View full text |Cite
|
Sign up to set email alerts
|

Conformational trapping of Mismatch Recognition Complex MSH2/MSH3 on repair-resistant DNA loops

Abstract: Insertion and deletion of small heteroduplex loops are common mutations in DNA, but why some loops are prone to mutation and others are efficiently repaired is unknown. Here we report that the mismatch recognition complex, MSH2/MSH3, discriminates between a repair-competent and a repair-resistant loop by sensing the conformational dynamics of their junctions. MSH2/MSH3 binds, bends, and dissociates from repair-competent loops to signal downstream repair. Repair-resistant Cytosine-Adenine-Guanine (CAG) loops ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 45 publications
6
84
0
Order By: Relevance
“…It was subsequently suggested that the Msh2-Msh3 complex binds CAG hairpins, inhibiting Msh3 ATPase activity and slowing down release of the complex from the hairpin [24], although this last point is still controversial [25]. It was subsequently shown that the human MSH2-MSH3 complex discriminates between repair-competent loops and repairresistant loops, such as those formed by long CAG repeats [26]. More recently, it was shown that short CAG/CTG slip-out structures were efficiently repaired by human MutL and MutS complexes [27,28], and to a lesser extent by MutS [27].…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently suggested that the Msh2-Msh3 complex binds CAG hairpins, inhibiting Msh3 ATPase activity and slowing down release of the complex from the hairpin [24], although this last point is still controversial [25]. It was subsequently shown that the human MSH2-MSH3 complex discriminates between repair-competent loops and repairresistant loops, such as those formed by long CAG repeats [26]. More recently, it was shown that short CAG/CTG slip-out structures were efficiently repaired by human MutL and MutS complexes [27,28], and to a lesser extent by MutS [27].…”
Section: Introductionmentioning
confidence: 99%
“…Error occurs through two proposed models; 1) the MutSβ (MSH2 and MSH3 complex) entrapment/hairpin escape model 2) the dysregulated strand directionality model. Both provide attractive arguments for a role of mismatch repair in TNR expansion, as both models propose impaired or dysregulated function of MutS, with the second also accounting for the MutL function [31][32][33]. Taken together, it can be seen why the presence of both slip-strand mispairing and mismatch repair creates a 'perfect genetic storm' , where an error in transcription is introduced and the exact mechanism supposedly responsible for correcting the mutation unwittingly aids in its formation.…”
Section: Mutagenic Mismatch Repairmentioning
confidence: 98%
“…It has been found that formation of non-B form DNA secondary structures such as hairpins, triplexes and tetraplexes is responsible for TNR expansion and deletion during DNA replication, repair, recombination and gene transcription (4,85,86,140,198,260). The secondary structures formed in a newly synthesized strand or damaged strand of the genome usually result in replication fork stalling (4,107), pausing of DNA polymerases and DNA slippage (4,108), trapping of mismatch repair proteins (113,114), inhibition of flap endonuclease 1 (FEN1) processing of a hairpin (111,167,261) and disruption of coordination among repair enzymes (115), and this ultimately leads to TNR expansion. In contrast, TNR secondary structures formed at the template strand during DNA repair promote DNA polymerases to skip over the structures, and this causes TNR deletion.…”
Section: Discussionmentioning
confidence: 99%
“…If a single-strand DNA breaks occurs during DNA lagging strand maturation and DNA repair, a downstream 5'-TNR-containing flap can fold back and form a hairpin structure that inhibits flap cleavage by FEN1 (110)(111)(112). In addition, a mismatch repair protein complex, MSH2/MSH3 can be trapped by hairpin structures (113,114) and stabilize the hairpin structure promoting TNR instability. Formation of a hairpin structure can also disrupt the coordination among DNA repair proteins that sustains an efficient DNA repair.…”
Section: Tnr Instability and Dna Repairmentioning
confidence: 99%